Penentuan Model Kesetimbangan Adsorpsi Ion Pb(II) Menggunakan Regenerated Spent Bleaching Earth (RSBE) - Sasmitra, Dani; Yusnimar, Yusnimar; Fadli, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Spent bleaching earth (SBE) is a waste produced by the bleaching unit in the palm oil refinery industry. One of the efforts to tackle SBE waste is regenerated into regenerated spent bleaching earth (RSBE) which can be used as an adsorber of heavy metals in water waste such as Pb(II) from industry. This study aims to determine the characteristics of the SBE and RSBE, the adsorption equilibrium time, the adsorption capacity of the RSBE with variations in the concentration of Pb(II) ion and the adsorption temperature and determine the appropriate adsorption isotherm model. In this study, SBE was regenerated by extracting oil by soxletation at 72oC for 5 hours with n-hexane solvent, followed by washing with 3% HCl and then physically activated at 470oC for 12 hours. A total of 1 gram of RSBE was mixed with Pb(II) solution with a volume of 100 ml at various concentrations (20, 30 and 40 ppm) and adsorption temperatures (40, 50 and 60Â°C). The results showed that the absorption of Pb(II) ion by RSBE reaches equilibrium after 150 minutes contact time and the adsorption that occurs follows the Langmuir isotherm adsorption model with a correlation coefficient (R2) value of 0,9935 and a maximum absorbing capacity value of 4,29 mg Pb(II)/g RSBE that occurs at variations in the concentration of 40 ppm and a temperature of 60Â°C. Keywords: adsorption, adsorption isotherm, Pb(II) ion, RSBE, SBE.